(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Foreign language teaching is gaining popularity in recent years. However it is not easy to teach foreign language through second language. Very often students coming from different background with different mother tongues sit under one roof to learn foreign language. To be a successful foreign language teacher, one must first know the goals of the learners then only effective methodologies can be adopted. The goal of school student’s university students and professional’s learners cannot be put in one single box. Hence we need to different approaches while dealing with different personals of the society. There are three teaching methods that dominate language teaching the Direct Method, the Grammar-Translation Method, and the Audio-Lingual Method. The nature of a student’s goals and characteristics feature of the target language will determine which is best to follow while teaching.In the late last century Indian students were very keen to learn French and German. This led to the establishment of Alliance Francaise to learn French and Max Mueller Bhavan for German in India. However in the new century the scenario is somewhat different. The rise of China as global power has given new hopes and aspiration to young Indian students to learn Chinese language. Hence this paper will try to find the best possible methods to teach Chinese language in India especially in Universities.